A framework for compensating rest allowance - Belbin, R. M. (College of Aeronautics, 1955)
A great many papers have been written on the subject of human fatigue but the complaint is often made in industry that, while many of these studies may be of scientific value, it is very difficult to see how they may assist those who are concerned with the problem in industry, in particular the time study engineers whose job it is to assess the fatigue that work involves and to apply the appropriate allowances. The object of this paper is to consider the problem of these allowances (usually termed. Compensating Rest or C.R. allowances) in the light of scientific evidence. It is not proposed to refer to previous work that bears on this field in any specific way, since a paper which did so would run to considerable length, but rather to evaluate some of the most important material and to suggest the type of framework for C.R. allowances that would appear most rational in the light of available evidence. As this paper is written primarily for those in industry, knowledge of industrial practices and terminology is assumed.